Recent Issues and Problems in Bangladesh-India Relations: A Bangladeshi Perspective - Huq, Md. Ershadul (European Scientific Journal, ESJ, 2023)
The relationship between India and Bangladesh has steadily grown in recent years, particularly after Bangladesh Prime Minister Sheikh Hasina took office in January 2009. Indian Prime Minister Narendra Modi praised the relationship as a "golden period" in 2019. Indeed, Bangladesh is crucial to India’s "Neighborhood First" and "Act East" policies and has played a critical role in sustaining peace and security in the country’s Northeast region. However, despite their mutual goodwill, there is some pessimism regarding the relationship’s future. This article examines the historical evolution of India-Bangladesh relations, the diverse perspectives on the relationship (Economic et al.), Bangladesh’s significance to India, and the issues that threaten to cloud India-Bangladesh ties. Through this research, we can easily see the recent India-Bangladesh relations, whether it moves steadily or not. We can also discover the problematic issues that still exist and cause mistrust between both countries. Finally, give a precise scenario for the country’s policymakers that this tie is essential for both countries and should be stronger only when policymakers give more importance and resolve these problems as soon as possible.